Regional Targeting of the Economic Policy of the Russian Federation as an Institution of Regional Spatial Development - Alexander Ivanovich Tatarkin (Экономика региона, 2016)
In the article, the task to evaluate the condition of the Russian economy amid slumping energy prices and «exchange of sanctions» is addressed. It also aimes to define the priority directions of the economic policy of the Russian Federation as the full-service institutions capable to maintain the stability and consistency of development. The process of ensuring the spatial structure development of the Russian territories by means of involvement in the development processes the regional and municipal opportunities is offered to initiate with the optimization of the inter-budgetary relations of «municipality — region — federal centre.» All Russian citizens are recommended to treat more strictly and more responsibly the Constitution as the Basic Law supported by the populace and defining the strategic development priorities of the country on a long-term outlook. The methodology of the optimization of the inter-budgetary relations between the Federation, its subjects and municipalities is proved by the evidence-based delineation of powers and responsibility of each level for socio-economic results of work. It is offered to develop the national plan of socio-economic and social development engaging in work the experts and public; its main priorities have to be the improvement of the quality and productivity of the public administration and the spatial structure of the Russian territories. The mechanisms and institutions that help to involve the regions and territories to the implementation of the national plan are proved. The findings and recommendations offered in the paper may be used by the federal authorities in the development and adoption of laws and other regulations on the distribution of authority and optimization of the budgetary process. They are also may be useful for the regional and municipal authorities for the planning and development of the regional spatial structure.